Communication Strategy : a Need of Sustainable Development - JFM Perspective - Rastogi, Alind (Indian Forester, 1995)
The new Forest Policy 1988 envisages people's participation in management of existing treasure of biodiversity in the country. As per policy directive the concept of participatory forest management is sweeping the entire nation. Today the forest field functionaries have not only to act as natural resource managers but also as facilitators of community participation in sustainable development, protection and conservation offorest wealth. Forfacjlitating community participation and involving people in decision making and planning, a suitable communication strategy is to be evolved. The paper stresses upon the need for evolving effective communication systems by the Forest Department.